(untitled) - Dent, Harry S. (New York, 1993)
Predicting the decline of Japan and the re-emergence of the United States as the most powerful economy on the planet, the Harvard economist offers readers practical advice on taking advantage of the situation.
Keywords: United states,Economic; Economic conditions,Forecasting; 1981; United states